Effect of spider mite infestation on cotton yield in cotton cultivation. (International conference on multidisciplinary science, 2023)
In this thesis, the damage caused by the spider mite to cotton is scientifically based on statistical analysis and the work done in this field is covered in detail. Spider mite is one of the dangerous pests that damage the cotton crop. Today, duya scientists have studied a lot about the effects of spider mites on cotton cultivation. This research is also a logical continuation of these researches. In this article, the damage of the spider mite to the cotton crop is explained with clear examples.